2022
DOI: 10.3390/gels8070421
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Gene-Activated Sodium Alginate Hydrogel Scaffolds

Abstract: Gene therapy is one of the most promising approaches in regenerative medicine to restore damaged tissues of various types. However, the ability to control the dose of bioactive molecules in the injection site can be challenging. The combination of genetic constructs, bioresorbable material, and the 3D printing technique can help to overcome these difficulties and not only serve as a microenvironment for cell infiltration but also provide localized gene release in a more sustainable way to induce effective cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The combination of mineralized collagen, sodium alginate (SA) hydrogels with positive osteogenic effects addressed the challenge of achieving uniform distribution on material surface. 43,44 Therefore, in the current study, we utilized substrate materials with enhanced osteogenic activity and modified bioactive glass nanoparticles to improve biological activity and uniform distribution through sodium alginate (SA) hydrogel. This approach leveraged the strengths of both materials to achieve superior osteogenic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of mineralized collagen, sodium alginate (SA) hydrogels with positive osteogenic effects addressed the challenge of achieving uniform distribution on material surface. 43,44 Therefore, in the current study, we utilized substrate materials with enhanced osteogenic activity and modified bioactive glass nanoparticles to improve biological activity and uniform distribution through sodium alginate (SA) hydrogel. This approach leveraged the strengths of both materials to achieve superior osteogenic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is aimed at a comparative assessment of neo-osteogenesis in critical-sized bone defects using SA-based hydrogel scaffolds fabricated by 3D cryoprinting. We have previously demonstrated that 3D cryoprinted gene-activated scaffolds maintain cell viability and provide a prolonged plasmid release in a high concentration sufficient for the effective transfection of cells in vitro and in vivo [ 43 ]. The focus of this study is on implementing the developed universal platform to form GASs in which the model plasmids were replaced with therapeutic ones for efficient bone regeneration enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Gene-activated sodium alginate scaffolds were fabricated using 3D cryoprinting as described earlier [ 43 ]. Briefly, 8 mg of SA was dissolved in 92 µL of distillated H 2 O, containing 20 µg pDNA/60 µg PEI for in vitro study and 100 µg pDNA/300 µg PEI for in vivo study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone tissue engineering in situ through BM-MSCs osteogenic differentiation may be performed using immobilized gene delivery nanocomplexes [ 58 ]. Bioactive scaffolds with modified surface properties or gene-activated materials have promising applications as scaffolds for cell seeding [ 59 , 60 ].…”
Section: Materials For Bone Tissue Engineering In Situmentioning
confidence: 99%